FACTORS ASSOCIATED WITH BLOOD PRESSURE ON SHIFT WORKERS AND NON-SHIFT WORKERS IN PT. X GRESIK - Nur Fitriani; Neffrety Nilamsari (Universitas Darussalam Gontor, 2017)
Blood pressure is a critical factor in the circulation system. There are two kinds of blood pressure abnormality known as hypertension or high blood pressure and low blood pressure or hypontension. Many risk factors to enhace it, or person who suffering hypertension, one of them shift work. A research about Malaysian male workers in a firm showed that the prevalence of shift work related to hypertension was significantly higher shift worker than non-shift worker. The result of Medical Check Up PT. X Gresik worker on 2017, that shift worker and non-shift have hypertension risk approxiametly 15.75 % or 26 workers. The purpose of this research, knowing the factors related to blood pressure on shift worker or non-shift worker in PT. X Gresik. This research cross-sectinal designed with 44 workers into 2 grohups and its selected to use purposive sampling. Data taken by through measurement and questionnaire. The data analysis are univariate analysis with cross tabulation and bivariate analysis with statistic test, its chisquared test and spearmen correlation. The result explained that shift worker and non-shift worker who have normal blood pressure 34.1 %, pre hypertension, 52.2%, and hypertension stage one 13.6%. In this research, significantly statistic of the history of family disease and body massa index are correlated to blood pressure (p<0.05). While the age, education level, job stress, physical activity, caffeine consumtion, drugs ingestion, and smoking habit are significantly statistic uncorrelated to blood pressure (p>0.05). Based on research, it would be suggest to a company provide routine health service, and workers to check routinely blood pressure tension, to set diet with balanced nutrition. Keywords : Blood pressure, Shift and non-shift workers, PT. X Gresik